Nymphal performance and fecundity of melanaphis sacchari (Zehntner) (Hemiptera: Aphididae) in different sorghum genotypes - Canassa, Vinicius Fernandes [UNESP]; Baldin, Edson Luiz Lopes [UNESP] (Entomology & Applied Science Research Letters-easletters, 2022)
Sorghum [Sorghum bicolor (L.) Moench] is a tropical grass native to the African continent that is often used as human and animal feed. Polyphagous insects such as the sugarcane aphid, Melanaphis sacchari (Zehntner) (Hemiptera: Aphididae), have benefited from the increase of sorghum planted in Brazil, the United States (US), and around the world. This study evaluated the performance of nymphs and adult fecundity of sugarcane aphids in 12 sorghum genotypes to find sources of resistance to the aphid while considering the current lack of efficient control methods that are less aggressive to the environment. Each repetition consisted of a single sorghum seedling infested with 10 nymphs in the first instar, in no-choice tests, totaling 10 replicates per genotype. The pre-reproductive period, nymphal period, daily and total nymph production, nymphal viability, percentage of adult emergence, and wax content were evaluated. After five days of confinement, the plants were evaluated, counting the number of adults present in the seedlings. All genotypes compromised the biological performance of M. sacchari. The genotypes 84P68, CHR 2042, DKS 3707, HG35W, M60GB31, SP73B12, and 95207 induced 100% of nymphal mortality. No difference was found between genotypes in the wax content on the sorghum leaves. These results are important for the species M. sacchari and may provide subsidies for future breeding programs, focusing on sorghum resistance to aphids.
Keywords: Sugar cane aphid; Sorghum bicolor; Host-plant resistance; Nymphoposition